AKTIVITAS ANTIOKSIDAN DAUN PEGAGAN (Centella asiatica L. Urban) DAN BUNGA KRISAN (Crhysanthemum sp.) PADA TIGA VARIASI SUHU PENGERINGAN - Dini Yulianti (Pasundan Food Technology Journal (PFTJ), 2020)
Abstract This research aims to determine the effect of dryer temperature variations on the antioxidant activity of gotu kola leaves and chrysanthemum flowers. The research method used was the experimental method using Randomized Block Design (RBD) with 6 types of treatments and 2 replications. The drying process is carried out until it reaches the moisture content according to SNI for dry tea which is a maximum of 8%. Drying is done using a food dehydrator with three temperature variations (50°C, 55°C and 60°C). The results show that the higher the drying temperature, the faster the standard moisture content is reached. The higher the drying temperature, the weaker antioxidant activity produced. The best antioxidant activity was obtained using the 50°C drying temperature of 36.1 ppm for gotu kola leaf simplicia. While the best antioxidant activity of simplicia of chrysanthemum flowers was obtained at 50°C at 137.99 ppm. The six samples showed positive results on the flavonoid test. Keywords: Antioxidant activities; chrysanthemum flower; gotu kola leaf